Zero history [compact disc, unabridged] - Gibson, William, 1948- (Penguin Group USA, 2010)
Two people trail in the wake of Bigend, the global marketing genius: a former singer-turned- journalist who can't say no to him; and a former addict, useful because he's brilliant, watchful, and essentially invisible. Bigend needs these people to help him stay on top of the global market. Because clearly someone wants to push him off it.